cADPR and NAADP: messengers for calcium signalling - Galione, Antony (Henry Stewart Talks, 2007)
Calcium signaling mechanisms, Calcium stores and calcium mobilization, Intracellular calcium release channels, cADPR as an intracellular messenger, Ryanodine receptors, Cardiac excitation, Coupling, NAADP, Acidic calcium store, Smooth muscle cell calcium signaling, Calcium spiking, NAADP receptors